2008
DOI: 10.1080/08916930701620100
|View full text |Cite
|
Sign up to set email alerts
|

Anti-thyroid antibodies and thyroid dysfunction in rheumatoid arthritis: Prevalence and clinical value

Abstract: Our study shows an increased prevalence of anti-thyroid antibodies in RA patients with a low prevalence of hormonal alterations. However, anti-thyroid antibodies do not seem to identify any peculiar RA phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 18 publications
3
46
2
5
Order By: Relevance
“…A study on an Italian population showed high occurrence of thyroid autoantibodies with low prevalence of hormonal alterations. 45 A meta-analysis on the prevalence of thyroid autoantibodies showed that there was increased prevalence of Tg and TPO antibodies, with OR of 3.1 and 2.3 respectively. 11 Nevertheless, when a subgroup analysis according to patients' geographical location was done, it showed that the American RA population did not have an increased rate of antithyroid antibodies, thus emphasizing the need for local studies.…”
Section: Discussionmentioning
confidence: 99%
“…A study on an Italian population showed high occurrence of thyroid autoantibodies with low prevalence of hormonal alterations. 45 A meta-analysis on the prevalence of thyroid autoantibodies showed that there was increased prevalence of Tg and TPO antibodies, with OR of 3.1 and 2.3 respectively. 11 Nevertheless, when a subgroup analysis according to patients' geographical location was done, it showed that the American RA population did not have an increased rate of antithyroid antibodies, thus emphasizing the need for local studies.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical observations demonstrated that co-manifestation of autoimmune disease within a single patient occurs more frequently than combined prevalence of underlying diseases predicts (7). Furthermore, patients with autoimmune disease are prone to develop additional autoantibody reactivities, for example an increased frequency of (i) anti-thyroid antibodies were found in rheumatoid arthritis (8); (ii) antinuclear antibodies (ANA) in pemphigus (9); or (iii) anti-CCP antibodies in rheumatoid arthritis (10). In contrast, it is not known whether different autoantibodies co-occur in individuals who are clinically healthy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that MSCs have pleiotropic immunomodulatory effects, including the inhibition of T cell proliferation (4-6), suppression of natural killer (NK) cell proliferation (7), modulation of cytokine production (8), and inhibition of dendritic cell (DC) maturation (9,10). Although many soluble factors such as transforming growth factor-beta (TGF-b) (11,12) and IL-10 (13) have been reported to be involved in the immunomodulatory effects of MSCs, the exact mechanism underlying immunosuppression by MSCs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…SGTD manifested as a "joint syndrome", which has not only the subjective and objective manifestations [8,9].…”
Section: Discussionmentioning
confidence: 99%